Cheques sent in settlement - Andrews, David W. (London : Waterlow, 1991)
This book is a result of the investgation on every aspect of cheques sent in settlement and other related issues.
Includes index.
oif 02/03/15
Loan
Keywords: Negotiable instruments -- England -- 1991.; Cheques -- Great Britain; Bills of exchange -- Great Britain. Banking law -- Great Britain; Debts -- Payment -- Law; Credit -- Law and legislation -- Great Britain